PENGARUH BUNGA PASAR, JATUH TEMPO OBLIGASI, RATING OBLIGASI, NILAI TUKAR DAN INFLASI TERHADAP YIELD OBLIGASI DI BURSA EFEK INDONESIA - sam'ani - (LPPM STIE DHARMAPUTRA SEMARANG, 2010)
This research investigates the effect of BI rate, term to maturity, bond rating, exchange rate and inflation to bond yield. The proxies of BI rate, term to maturity, bond rating, exchange rate and inflation are independent variables, and the dependent variable is bond yield. The research uses the sample of corporate conventional bonds listed in Indonesia Stock Exchange (IDX) and rated by Pefindo during 2000 – 2008 , while data of market interest rate (BI rate), exchange rate and inflation provided from Bank Indonesia and data statistik Indonesia. It suggest that correlation between bond yield with BI rate, term to maturity, bond rating, exchange rate and inflation are 0,640. While coefficient determination ( R Square) equal to 0,409, its meaning 40,90 % bond yield explainable by interest rate (BI rate), term to maturity, bond rating, exchange rate and the inflation, the rest (59,10%) explained by others factor. The result suggest, that BI rate, term to maturity, bond rating, exchange rate and inflation have a significant effect to bond yield with 0,000 < α = 0,05. The existence of BI rate and term to maturity have possitive significant effect to bond yield. The existence of bond rating and exchange rate have negative significant effect to bond yield and inflation has no significant effect to bond yield. Keyword : Bond yield, BI Rate, term to maturity, bond rating, exchange rate and inflation